2017
DOI: 10.1142/s0219887817500670
|View full text |Cite
|
Sign up to set email alerts
|

Conformal, concircular, quasi-conformal and conharmonic flatness on normal complex contact metric manifolds

Abstract: Conformal, concircular, quasi-conformal and conharmonic curvature tensors play an important role in Riemannian geometry. In this paper, we study on normal complex contact metric manifolds under flatness conditions of these tensors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…A concircularly flat spacetime is of constant curvature. As a result, the deviation of a spacetime from constant curvature is measured by the concircular curvature tensor M. Researchers have shown the curial role of the concircular curvature tensor in mathematics and physics (for example, see [2][3][4][5][6] and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…A concircularly flat spacetime is of constant curvature. As a result, the deviation of a spacetime from constant curvature is measured by the concircular curvature tensor M. Researchers have shown the curial role of the concircular curvature tensor in mathematics and physics (for example, see [2][3][4][5][6] and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Conformal and concircular curvature tensors on contact manifolds have been studied in [23][24][25]. M-projective curvature tensor on manifolds with different structures studied by many authors [26][27][28].…”
Section: Theoremmentioning
confidence: 99%
“…Let M be a M-projectively flat normal metric contact pair manifold , then, from (25), M is conformally flat if and only if…”
Section: Theorem 11mentioning
confidence: 99%
“…De et al [27] showed that, in a conharmonically flat spacetime with cyclic parallel Ricci tensor, the energy-momentum tensor is cyclic parallel and conversely. The flatness conditions of the conharmonic curvature tensor on normal complex contact metric manifolds were studied by Vanli and Unal [28]. Yildirim [29] proved that certain types of complex κµ spaces cannot be conharmonically flat.…”
Section: Introductionmentioning
confidence: 99%